Modern Tendencies in the Development of the Energy Industry - Saitkamolov Mukhammadkhuja Sobirkhuja ugli (Zien Journals, 2022)
The article deals with renewable energy sources covering a number of different types of primary energy (solar energy, wind energy, biomass, water flows, geothermal heat, waste), the largest development rates in the world are currently achieved by China, India and the USA
Keywords: energy industry; green energy; electricity; hydropower